Design of Parking Information System in Langsa City General Hospital, Aceh - Nurul Azqa Mayor; Rina Kurniawati (Politeknik Piksi Ganesha Indonesia, 2023)
This study designed and built a parking information system at the Langsa City General Hospital with the aim of facilitating the management of incoming and outgoing vehicle data at the Langsa City General Hospital parking lot in Aceh. With the rapid advancement of technology, previous data management was still done manually, so it was not effective and efficient, and officers found it very difficult to know the data of incoming and outgoing vehicles. Researchers designed a computer-based information system to facilitate the management of the parking system. Methods of data collection using descriptive qualitative methods, namely observation, interviews, and literature study, and software development methods using the waterfall as well as the PHP programming language and the MYSQL database The information system created aims to make it easier for officers to manage vehicle entry and exit data at the Langsa City Regional General Hospital in Aceh.